Preliminary Psychometrics of the Neurological Disorders Depression Inventory for Epilepsy–Youth. (November 2013) - Wagner, Janelle L.; Smith, Gigi; Ferguson, Pamela L.; Fedele, David A.
The authors examined the preliminary psychometrics of a depression screening tool for youth with epilepsy. Development involved content analysis, cognitive interviewing, and qualitative analysis. Ninety-three youths with epilepsy aged 10 to 17 years completed the Neurological Disorders Depression Inventory for Epilepsy–Youth and the depression module of a standardized clinical interview. Caregivers rated seizure severity and completed the Pediatric Symptom Checklist. Results indicated strong reliability indices, including test-retest, κ value, and internal consistency for the Neurological Disorders Depression Inventory for Epilepsy–Youth. It was significantly associated with the other measures of depression and psychosocial functioning. Factor analyses revealed a 1-factor solution for 9 items, with 35.7% of the variance explained. An optimal cutoff score of 27 resulted in a sensitivity index of 0.80 and a specificity index of 0.71. The Neurological Disorders Depression Inventory for Epilepsy–Youth is a screening tool that can be utilized in routine epilepsy care, but further evaluation is necessary.